Avaliação ultra-sonográfica convencional e dopplerfluxométrica durante a fase folicular do ciclo estral de cadelas - Bicudo, Alexandre Luiz Costa [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Lopes, Maria Denise [UNESP]; Vulcano, Luiz Carlos [UNESP]; Derussi, Ana Augusta Pagnano [UNESP] (My University, 2010)
No clinical evaluation on the mating receptivity for the male is a safe method to detect with exactness the occurrence of ovulation. Some females can ovulate in the fifth day of the oestral cycle, while in others ovulation can occur until the thirtieth day. The most recently technique to determine ovulation on bitches is the ovary exploration by ultrassonography. Therefore, the aim of this work was to evaluate the dynamics on the follicular development in bitches by conventional ultrassonography and determinate the dopplerfluxometric values of the intraovarian artery, in order to detect with security the ovulation on bitches. For this, 05 bitches at the beginning of proestrous had been used, submitted to serial examinations ultrassonography. It was evaluated the development of 07 follicles since the initial growth until the formation of the corpora lutea, using ultrasound on B mode with a 10Mhz transducer. The conventional ultrassonography image made it possible to follow the follicular development and/or collapse and formation of corpora lutea in 85.7% of the follicules observed. The use of the Doppler technique was possible during all the period of proestrous and estrous and the average of the maximum velocity of the sistolic peak of the intra-ovarian artery was 26.41cm/s. The resistance index (IR) presented a decline at the day of ovulation until 24 hours, and its value varied of 0.44 ± 0.59 in this period. The IP presented oscillations with decline since 120 hours before until 24 hours after the ovulation and its value in this period was 0.57±1.1.

Ninguna evaluación clínica o la recepitividad a la cubricionón por el macho son métodos seguros para ocurrencia y el día de la ovulación en las perras. Algunas hembras pueden ovular en el quinto día del ciclo estral, mientras que en otras la ovulación puede ocurrir hasta el trigésimo día. La técnica más reciente para determinar la ovulación en la perra es la exploración ovariana por ultrasononido. Por lo tanto, este presente trabajo tuvo por objetivo evaluar la dinámica del desarrollo folicular en perras por el examen ultrasonográfico convencional y determinar los valores dopplerflujométricos de la artéria intraovariana, para detectar con seguridad la ovulación en las perras. Fueran utilizadas 05 perras en el inicio de la fase proestro, sometidas a exámenes ultrasonográficos seriados. Fueran evaluados el desarrollo de 07 folículos desde el crecimiento inicial hasta la formación del cuerpo lúteo, utilizando ultrasonido en el modo B con transductor de 10 Mhz. La imagen ultrasonográfica convencional posibilitó acompañar el desarrollo folicular y o colapso y formación del cuerpo lúteo en 85,7 % de los folículos observados. El uso de la técnica Doppler fue posible durante todo el período del proestro y estro y el promedio obtenido de la velocidad máxima del pico sistólico da la artéria intraovariana fue de 26,41 cm/s. El índice de resistência (IR) presentó un declive en el día de la ovulación hasta 24h después, y su valor varió de 0,44- 0,59 en este período. El IP presentó oscilaciones con declive desde 120 horas antes hasta 24 horas después de la ovulación y su valor en ese período fue de 0,57 1,1.

Nenhuma avaliação clínica ou a receptividade à cobrição pelo macho são métodos seguros para detectar com exatidão a ocorrência e o dia da ovulação nas cadelas. Algumas fêmeas podem ovular no quinto dia do ciclo estral, enquanto em outras a ovulação pode ocorrer até o trigésimo dia. A técnica mais recente para determinar a ovulação na cadela é a exploração ovariana por ultra-sonografia. Portanto, o presente trabalho teve por objetivo avaliar a dinâmica do desenvolvimento folicular em cadelas pelo exame ultra-sonográfico convencional e determinar os valores dopplerfluxométricos da artéria intra-ovariana, para detectar com segurança a ovulação nas cadelas. Foram utilizadas 05 cadelas no início da fase de pró-estro, submetidas a exames ultra-sonográficos seriados. Foram avaliados o desenvolvimento de 07 folículos desde o crescimento inicial até a formação do corpo lúteo, utilizando ultra-som no modo B com transdutor de 10Mhz. A imagem ultra-sonográfica convencional possibilitou acompanhar o desenvolvimento folicular e ou colapso e formação de corpo lúteo em 85,7% dos folículos observados. O uso da técnica Doppler foi possível durante todo o período do pró-estro e estro e a média obtida da velocidade máxima do pico sistólico da artéria intra-ovariana foi de 26,41cm/s. O índice de resistência (IR) apresentou um declínio no dia da ovulação até 24 horas após, e o seu valor variou de 0,44 – 0,59 neste período. O IP apresentou oscilações com declínio desde 120 horas antes até 24 horas depois da ovulação e seu valor nesse período foi de 0,57 ±1,1.
Conventional ultrasound examination and dopplerfluxometry of ovarian of bitch, during the follicular phase of the oestral cycle
Evaluación del ultrasonido convencional y dopplerflujometrica durante la fase folicular del ciclo estral de perras
Keywords: Ovary; Doppler; Follicule; Estrous; Bitch; Ovary; Doppler; Follicule; Estrous; Bitch; Ovário; Doppler; Folículo; Estro; Cadelas